NOTASI ETNIS DAN KEBANGSAAN DALAM DDC 23 TABEL 5: SUATU DOKUMEN TENTANG ETNIS DAN KEBANGSAAN INDONESIA - Wartini Wartini; Sri Mulyani (Ikatan Pustakawan Indonesia, 2014)
Several collections of National Library an the subject of ethnic and national groups of lndonesia have not been given classification numbers classification numbering is not in accordance with to the right ethnic groups topics, Due to the notation used under the class of -992 2 and even some of the collection & classed in general number with additional notation geographic area from Table 2. Expansion number for the ethnic and nation groups of lndonesia need to be done, because in Indonesia there ore many diverse ethnic groups and customs. The expansions number will make the librarians easier to determine appropriate notation and consistence with the topics of the materials.